2022
DOI: 10.5539/hes.v12n3p114
|View full text |Cite
|
Sign up to set email alerts
|

Recommended Improvements for Online Learning Platforms Based on Users’ Experience in the Sultanate of Oman

Abstract: The Covid-19 pandemic has seen an increasing use of video conferencing software as e-learning platforms. Students and faculty members face many challenges in using these platforms as part of the teaching and learning process, including technical problems. This paper reviews these challenges and offers solutions to improve the experience. A descriptive-analytical approach was used, with the researchers collecting data from the literature and from questionnaires distributed to 32 faculty members and to 104 stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…It is clear from the results, that essay writing students face challenges represented by the lack of collaboration and lack of internet access, which affects their engagement and collaboration with their colleagues in the virtual environment. This is in line with previous studies byAlkubaisi et al (2022) andKarkar-Esperat (2018), who highlighted the importance of enhancing e-learning infrastructure and the equity of access to technological devices.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…It is clear from the results, that essay writing students face challenges represented by the lack of collaboration and lack of internet access, which affects their engagement and collaboration with their colleagues in the virtual environment. This is in line with previous studies byAlkubaisi et al (2022) andKarkar-Esperat (2018), who highlighted the importance of enhancing e-learning infrastructure and the equity of access to technological devices.…”
supporting
confidence: 92%
“…In light of these objectives, the fundamental aim of this research is to gauge the effectiveness of online first year composition courses designed for Jordanian English as a Foreign Language (EFL) students. The distinctive context of Jordan, characterized by substantial investments in technology and e -learning infrastructure (Alkubaisi et al, 2022) presents an intriguing and noteworthy case study. The overarching purpose of this study is to contribute to the ever-expanding body of knowledge pertaining to online education within the realm of EFL.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another empirical research involving students from the public and private HEIs of Oman showed that the students from the public HEIs were more satisfied with the online learning platforms than from the private HEIs, and in general, the students perceived poor internet connectivity, weak technical support, absence of measures to check the plagiarism of answers and cheating, lack of prior experience, improper focus and time management, etc. (Abdulsattar, Al-Kubaisi, Al-Saifi, & Al-Shidi, 2022). Also, the study pointed out that the teachers were not well-versed with the online learning platforms.…”
Section: Discussionmentioning
confidence: 95%
“…The study makes suggestions for enhancements to the user experience, delivering perceptions into the user's point of view and presenting workable ideas to enhance the experience of e-learning platforms. The studies by Alkubaisi et al (2022) and Kalugina and Timchenko (2023) shed light on the technological difficulties educators and students have when using online learning platforms. The results highlight how crucial it is to address technological challenges, user experience problems, and the psychological effects of digitalization.…”
Section: Theme-2 Technological Challengesmentioning
confidence: 99%